Embodying the music and death nexus : consolations, salvations and transformations - Bennett, Marie Josephine; Shadrack, Jasmine Hazel; Levy, Gary, active 2022 (Emerald interdisciplinary connexions, 2022)
Embodied encounters with death affect humans deeply, with the power to crush, transform and strengthen individuals and relationships. Understanding that these encounters often have a musical accompaniment, this edited collection offers a range of critical, analytic, discursive and personal reflections on how music provides both a container and a medium for experiencing, processing and integrating embodied encounters with death. The collection showcases new and original interdisciplinary case studies written by authors from several different countries across Australia, France, The Netherlands, Poland and the UK. Taking an international, interdisciplinary and inclusive approach, this carefully curated collection elaborates embodied encounters with death through music across a variety of praxes and disciplines such as death & grief, queer studies, disability, philosophy, and more. Providing a mix of personal perspectives and insights on the impact of music and death alongside more conventional academic studies, the chapters reveal how music and human nature are intimately, and bodily, entwined. Framed by opening and closing chapters written by the team of three editors, this core text in the field provides a unique overview of the implications and ramifications of the embodiment of death through music and the musicalisation of death through the body, and signposts possibilities for further research.